Self-assembled monomolecule taking spirofluorene as conjugated bridge as well as preparation method and application of self-assembled monomolecule
By developing self-assembled single-layer materials with spirofluorene as the conjugated bridge, the energy level mismatch and stability of hole transport materials in existing perovskite solar cells are solved, and the efficient hole extraction and photothermal stability of the material are achieved, and the efficiency and stability of the solar cell are improved.
Patent Information
- Application Number
- CN202411757687.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
In existing perovskite solar cells, hole transport materials with p-i-n structure such as nickel oxide and PTAA have energy level mismatch, interface defects and stability problems, which limit the improvement of battery performance.
A self-assembled single-layer material with spirofluorene as the conjugated bridge was developed. The types of conjugated bridges were adjusted to optimize self-assembly behavior, energy level regulation and photothermal stability through carbazole and its derivatives and phosphoric acid as functional groups and anchor groups.
The good light stability of the material and the efficiency of interface hole selection are improved, the photoelectric conversion efficiency and device stability of perovskite solar cells are improved, and the photoelectric conversion efficiency of more than 24% is achieved.
Smart Images

Figure CN119569778A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar energy and relates to the synthesis of self-assembling molecules, and specifically relates to a self-assembling single molecule with spirofluorene as a conjugated bridge and a preparation method thereof, and application of the self-assembling single molecule in perovskite solar cells. Background Art
[0002] As an emerging photovoltaic technology, perovskite solar cells (PSCs) have attracted attention due to their advantages such as simple manufacturing process, easy adjustment of materials and high cost-effectiveness. PSCs are mainly divided into two structures: nip and pin. The pin structure is more suitable for the production of large-area flexible, stacked and other solar cells because it can adopt low-temperature manufacturing processes and is compatible with a variety of carrier extraction layers, showing greater commercial potential. However, the key issues that need to be solved in the pin structure are to enhance the interface contact between the hole selective layer and the perovskite layer, improve the charge extraction and transfer between the interfaces, and reduce the accumulation of perovskite defects, which are crucial to improving the efficiency and long-term stability of perovskite solar cells. At present, the commonly used hole transport materials in pin structure perovskite solar cells include inorganic nickel oxide (NiO x ) and organic polymer PTAA. There is energy level mismatch and interface defects between nickel oxide and perovskite, which will lead to voltage loss and interface degradation. In addition, nickel oxide is a mixture, and its high-valent nickel ions will corrode perovskite and reduce the stability of battery devices. PTAA, on the other hand, is limited to further improve battery performance due to its high cost, unstable quality between product batches, poor film forming and wettability.
[0003] Therefore, the development of high-performance new hole transport materials is crucial to improving the performance of PSCs. As a hole transport material, self-assembled monolayer (SAM) is mainly composed of carbazole functional groups, alkyl chain bridging groups and phosphate anchoring groups. SAM materials have become a popular choice for the preparation of high-efficiency PSCs because of their simple structure, flexible design, low optical absorption, low material usage, and compatibility with stacked and flexible perovskite solar cells. Although the widely used PACz series SAMs have efficient hole extraction capabilities (Joule 2021, 5, 2915-2933), their insulating alkyl connecting bridges have poor stability in high-energy ultraviolet photons (Angew. Chem. Int. Ed. 2024, 63, e202315281). Therefore, there is an urgent need for a new SAM material that can both effectively extract holes and improve photostability, which is of great significance for promoting the industrialization of PSCs. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide a co-self-assembled monolayer material which has a simple structure, low cost, high hole transport performance and light stability, and is suitable for large-scale production.
[0005] In order to achieve this goal, the present invention adopts the synthesis strategy of self-assembled monolayer and develops a new type of self-assembled monolayer material. The material uses carbazole and its derivatives as functional groups and phosphoric acid as anchoring groups. By adjusting the type of conjugated bridge, the self-assembly behavior, energy level regulation and photothermal stability of the material are optimized. The design of this material not only ensures good photostability, but also improves the interface hole selection efficiency, which is of great significance for improving the efficiency and device stability of perovskite solar cells. This type of material has the following structural formula:
[0006]
[0007] Among them, R is a methoxy group or an alkane group, and the conjugated bridge is a spirofluorene-type conjugated bridge.
[0008] Furthermore, the self-assembled monomolecular material with spirofluorene as a conjugated bridge is selected from the compounds with the following structures:
[0009]
[0010] Among them, R is a methoxy group or an alkane group, and the conjugated bridge is a spirofluorene-type conjugated bridge.
[0011] A further improvement of the present invention is:
[0012] The method for preparing a self-assembled monomolecular material using spirofluorene as a conjugated bridge is characterized by comprising the following steps:
[0013] (a) allowing compound I to undergo a substitution reaction with a dibromo ring bridge to generate an intermediate II;
[0014] (b) allowing compound II to undergo a substitution reaction with diethyl phosphite to generate intermediate III;
[0015] (c) hydrolyzing compound III to generate target product IV, i.e., a self-assembled monolayer material;
[0016] The reaction equation is as follows:
[0017]
[0018] Among them, R is a methoxy group or an alkane group, and the conjugated bridge is a spirofluorene-type conjugated bridge.
[0019] A further improvement of the present invention is:
[0020] The specific process of step (a) is: dissolving compound I and dibrominated conjugated bridge in N,N-dimethylacetamide (DMAC), and causing substitution reaction under the action of base and catalyst to produce intermediate II; the molar ratio of compound I to dibrominated conjugated bridge is 1:1-10.
[0021] The specific process of step (b) is: heating compound II and diethyl phosphite to react in a 1,4-dioxane nitrogen atmosphere, and separating and purifying after the reaction to obtain intermediate III; the molar ratio of compound II to diethyl phosphite is 1:1 to 20.
[0022] In step (c), compound III and bromotrimethylsilane are mixed in dichloromethane, and a hydrolysis reaction is carried out under a nitrogen atmosphere. After the reaction is completed, the target product IV is obtained by slurrying and filtration; the molar ratio of compound III to bromotrimethylsilane is 1:5-15.
[0023] Furthermore, the base used in step (a) is potassium hydroxide or potassium carbonate, the catalyst is cuprous iodide, the reaction temperature is 100-200° C., and the reaction time is 4-12 hours; the reaction temperature in step (b) is 100-110° C., and the reaction time is 4-15 hours; and the reaction temperature in step (c) is 10-100° C., and the reaction time is 4-15 hours.
[0024] The above-mentioned self-assembled monolayer material with spirofluorene as conjugated bridge is used in perovskite solar cells.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention provides a self-assembled monolayer material with spirofluorene as a conjugated bridge, wherein carbazole and its derivative groups, and the conjugated bridge groups are all conjugated units, have good ultraviolet light tolerance, and can effectively improve the light stability of the material;
[0027] 2. This type of self-assembled monolayer material with spirofluorene as the conjugated bridge has a larger conjugated plane structure, which enhances the interaction between molecules and enables the molecules to form an orderly and compact self-assembled monolayer (SAM) on the ITO substrate, which is beneficial to the interface charge extraction and transmission.
[0028] 3. The application of a self-assembled monolayer material with spirofluorene as a conjugated bridge in perovskite solar cells provided by the present invention achieves a photoelectric conversion efficiency of more than 24% and exhibits good photothermal stability, which helps to promote the commercial development of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The molecular structure of a self-assembled monomolecular material prepared by the present invention with spirofluorene as a conjugated bridge;
[0030] Figure 2 The NMR spectrum of Me-CzF prepared by the present invention;
[0031] Figure 3 The NMR spectrum of MeO-CzF prepared by the present invention;
[0032] Figure 4 The NMR spectrum of MeO-CzSFO prepared by the present invention;
[0033] Figure 5 The JV curve of the perovskite solar cell prepared by using the Me-CzF prepared by the present invention as the self-assembled monolayer material;
[0034] Figure 6 The JV curve of the perovskite solar cell prepared by using the MeO-CzF prepared by the present invention as the self-assembled monolayer material;
[0035] Figure 7 The JV curve of the perovskite solar cell prepared by using the MeO-CzSFO prepared by the present invention as the self-assembled monolayer material; DETAILED DESCRIPTION
[0036] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0037] The present invention adopts the synthesis strategy of self-assembled monolayer and develops a new type of self-assembled monolayer material. The molecular structure of the material is as follows Figure 1 shown.
[0038] The following is a detailed introduction using formula Me-CzF, formula MeO-CzF, and formula MeO-CzSFO as examples.
[0039] Example 1: Synthesis of self-assembled monolayer material Me-CzF
[0040] The synthetic route is as follows:
[0041]
[0042] Synthesis of compound of formula 3:
[0043] In a 100mL single-mouth round-bottom flask, raw material 1 (1g, 4.2mmol), 2-bromo-7-iodo-9,9-dimethylfluorene (3g, 7.6mmol), cuprous iodide (260mg, 1.4mmol), potassium carbonate (1g) and solvent DMAC (15mL) were added in sequence, and the mixed solution was heated to 150°C and refluxed for 24h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 1.86g of the compound shown in formula 3 as a white solid with a yield of 70%. 1 H NMR (400MHz, CDCl3) δ7.95 (s, 2H), 7.89 (d, J = 7.9Hz, 1H), 7.69-7.60 (m, 3H), 7.58 -7.52(m,2H),7.38(d,J=8.3Hz,2H),7.30-7.24(m,2H),2.59(s,6H),1.57(s,6H).
[0044] Synthesis of compound of formula 4:
[0045] Add intermediate 3 (1 g, 2.2 mmol), palladium acetate (50 mg, 0.22 mmol), dppf (122 mg, 0.22 mmol), potassium acetate (660 mg, 6.6 mmol) and diethyl phosphite (165 mg, 1.2 mmol) to a 100 mL two-necked bottle in sequence. Add 15 mL of 1,4-dioxane to the solvent and heat to 110 ° C for 10 h. After the reaction solution is cooled to room temperature, dichloromethane and water are added for extraction. The organic phase is distilled under reduced pressure. The crude product is subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 2) to obtain 0.9 g of intermediate 4 as a white solid with a yield of 80%. 1 H NMR (400MHz, CDCl3) δ8.01-7.94(m,4H),7.90-7.82(m,2H),7.67(d,J=1.8Hz,1H),7.59(dd,J=8.1,2.0Hz,1H) ,7.39(d,J=8.3Hz,2H),7.29-7.24(m,3H),4.29-4.11(m,4H),2.58(s,6H),1.59(s,6H),1.40(t,J=7.0Hz,6H).
[0046] Synthesis of formula Me-CzF:
[0047] Under nitrogen protection, intermediate 4 (100 mg, 0.2 mmol), bromotrimethylsilane (367 mg, 0.32 mL) and 10 mL of dichloromethane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 10 h. The solvent was removed by vacuum distillation, and a white solid was obtained by beating to obtain 70 mg of the product with a yield of 75%. The hydrogen nuclear magnetic resonance spectrum is shown in the attached figure. Figure 2 shown. 1 H NMR (400MHz, CDCl3) δ7.91 (s, 5H), 7.59 (d, J = 39.7Hz, 2H), 7.31 (d, J = 20.9Hz, 3H), 7.18 (t, J = 9.8Hz, 2H), 2.53 (s, 6H).
[0048] Example 2: Synthesis of self-assembled monolayer material MeO-CzF
[0049] The synthetic route is as follows:
[0050]
[0051] Synthesis of compound of formula 6:
[0052] In a 100mL single-mouth round-bottom flask, raw material 5 (1g, 4.4mmol), 2-bromo-7-iodo-9,9-dimethylfluorene (1.6g, 6.6mmol), cuprous iodide (860mg, 4.6mmol), potassium carbonate (1g) and solvent DMAC (15mL) were added in sequence, and the mixed solution was heated to 180°C and refluxed for 12h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 0.8g of the compound shown in formula 6 as a white solid with a yield of 70%. 1 H NMR(400MHz, CDCl3)δ7.88(d,J=7.9Hz,1H),7.68-7.59(m,5H),7.54(dt,J=8.1,1.5H z, 2H), 7.41 (d, J = 8.9Hz, 2H), 7.09 (dd, J = 8.9, 2.4Hz, 2H), 3.99 (s, 6H), 1.57 (s, 6H).
[0053] Synthesis of compound of formula 7:
[0054] Add intermediate 6 (1g, 2mmol), palladium acetate (70mg, 0.3mmol), dppf (55mg, 0.1mmol), potassium acetate (600mg, 6mmol) and diethyl phosphite (165mg, 1.2mmol) to a 100mL two-necked bottle in sequence. Add 15mL of 1,4-dioxane to the solvent and heat to 110℃ for 10h. After the reaction solution is cooled to room temperature, dichloromethane and water are added for extraction. The organic phase is distilled under reduced pressure. The crude product is subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 2) to obtain 0.88g of intermediate 7 as a white solid with a yield of 80%. 1 H NMR (400MHz, CDCl3) δ8.00-7.95(m,2H),7.90-7.82(m,2H),7.66(d,J=2.0Hz,1H),7.61-7.55(m,3H),7.41(d, J=8.9Hz,2H),7.09(dd,J=8.9,2.6Hz,2H),4.30-4.13(m,4H),3.99(s,6H),1.60(s,6H),1.40(t,J=7.0Hz,6H).
[0055] Synthesis of MeO-CzF:
[0056] Under nitrogen protection, intermediate 7 (200 mg, 0.36 mmol), bromotrimethylsilane (634 mg, 0.55 mL) and 10 mL of dichloromethane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 10 h. The solvent was removed by vacuum distillation, and a white solid was obtained by beating to obtain 140 mg of the product with a yield of 75%. The hydrogen nuclear magnetic resonance spectrum is shown in the attached figure. Figure 3 shown. 1 H NMR (400MHz, DMSO) δ8.13(d,J=8.1Hz,1H),8.01(dd,J=7.7,3.1Hz,1H),7.91-7.83(m,4H),7.74(ddd,J=12.7, 7.7, 1.3Hz, 1H), 7.59 (dd, J = 8.1, 2.0Hz, 1H), 7.38 (d, J = 8.9Hz, 2H), 7.07 (dd, J = 8.9, 2.6Hz, 2H), 3.88 (s, 6H).
[0057] Example 3: Synthesis of self-assembled monolayer material MeO-CzSFO
[0058] The synthetic route is as follows:
[0059]
[0060] Synthesis of compound of formula 9:
[0061] In a 100mL single-mouth round-bottom flask, raw material 5 (1g, 4.4mmol), 2,7-dibromospiro (fluorene-9,9-oxanthene) (3.2g, 6.6mmol), cuprous iodide (230mg, 1.3mmol), potassium carbonate (1g) and solvent DMAC (15mL) were added in sequence, and the mixed solution was heated to 180°C and refluxed for 18h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 1.8g of compound 9 as a white solid with a yield of 70%. 1 H NMR (400MHz, CDCl3) δ7.97(d,J=8.1Hz,1H),7.73(d,J=8.1Hz,1H),7.61(dd,J=8.1,2.0Hz,1H) ,7.59-7.54(m,1H),7.51(d,J=2.4Hz,2H),7.37(t,J=2.0Hz,2H),7.28(s,1H),7.27(d,J=1.6Hz ,1H),7.26(s,2H),7.18(s,1H),7.16(s,1H),6.97(d,J=2.6Hz,1H),6.95(d,J=2.6Hz,1H),6.9 1(ddd,J=7.8,6.4,2.1Hz,2H),6.60-6.55(m,2H),3.94(s,6H),1.41(s,1H),1.33-1.27(m,4H).
[0062] Synthesis of compound of formula 10:
[0063] Add intermediate 9 (1g, 1.5mmol), palladium acetate (11mg, 0.05mmol), dppf (170mg, 0.3mmol), potassium acetate (450mg, 4.5mmol) and diethyl phosphite (125mg, 0.9mmol) to a 100mL two-necked bottle in sequence. Add 15mL of 1,4-dioxane to the solvent and heat to 110℃ for 10h. After the reaction solution is cooled to room temperature, dichloromethane and water are added for extraction. The organic phase is distilled under reduced pressure. The crude product is subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 2) to obtain 0.8g of intermediate 10 as a white solid with a yield of 80%. 1H NMR (400MHz, DMSO) δ8.38(d,J=8.2Hz,1H),8.27(dd,J=7.9,2.8Hz,1H),7.80-7.73(m,4H),7.41-7.30(m,7H),7. 11(d,J=8.9Hz,2H),6.99-6.91(m,4H),6.51-6.47(m,2H),4.00-3.90(m,4H),3.85(s,6H),1.13(t,J=7.1Hz,7H).
[0064] Synthesis of MeO-CzSFO:
[0065] Under nitrogen protection, intermediate 10 (100 mg, 0.14 mmol), bromotrimethylsilane (254 mg, 0.22 mL) and 10 mL of dichloromethane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 10 h. The solvent was removed by vacuum distillation, and a white solid was obtained by slurrying. The product was 70 mg and the yield was 76%. The H NMR spectrum is shown in the attached figure. Figure 4 shown. 1 H NMR (400MHz, DMSO) δ8.34(d,J=8.1Hz,1H),8.18(dd,J=7.8,2.9Hz,1H),7.85-7.70(m,4H),7. 46-7.23(m,6H),7.12(d,J=8.9Hz,2H),7.02-6.88(m,4H),6.49(d,J=7.3Hz,2H),3.84(s,6H).
[0066] Example 4: This example provides an application of the Me-CzF compound prepared in Example 1 in the preparation of a perovskite solar cell. Test light source: AM 1.5 (solar simulator-Oriel91160-1000, 300W), data acquisition using Keithley 2400 digital source meter. Test results are attached Figure 5 The short-circuit photocurrent density of the battery device reached 25.62 mA cm -2 , the open circuit voltage is 1.195V, the fill factor (FF) is 0.791, and the photoelectric conversion efficiency reaches 24.22%.
[0067] Example 5: This example provides an application of the MeO-CzF compound prepared in Example 2 in the preparation of perovskite solar cells. Test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), data acquisition using Keithley 2400 digital source meter. Test results are attached Figure 6The short-circuit photocurrent density of the battery device reached 25.38 mA cm -2 , the open circuit voltage is 1.195V, the fill factor (FF) is 0.796, and the photoelectric conversion efficiency reaches 24.14%.
[0068] Example 6: This example provides an application of the MeO-CzF compound prepared in Example 3 in the preparation of perovskite solar cells. Test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), data acquisition using Keithley 2400 digital source meter. Test results are attached Figure 7 The short-circuit photocurrent density of the battery device reached 25.51 mA cm -2 , the open circuit voltage is 1.194V, the fill factor (FF) is 0.805, and the photoelectric conversion efficiency reaches 24.52%.
[0069] This method is only to illustrate the technical concept and characteristics of the present invention, and is intended to enable people proficient in this field to understand and implement the present invention, and is not intended to limit the scope of protection of the present invention. Any equivalent substitution or adjustment based on the core concept of the present invention should be included in the protection scope of the present invention.
Claims
1. A self-assembled monolayer material with spirofluorene as a conjugated bridge, characterized in that: The general structural formula is shown below: Among them, R is a methoxy group or an alkane group, and the conjugated bridge is a spirofluorene-type conjugated bridge.
2. The self-assembled monolayer material with spirofluorene as a conjugated bridge according to claim 1, characterized in that: A compound selected from the following structures: Among them, R is a methoxy group or an alkane group, and the conjugated bridge is a spirofluorene-type conjugated bridge.
3. A method for preparing a self-assembled monolayer material with spirofluorene as a conjugated bridge according to claim 1 or 2, characterized in that: The following steps are involved: (a) allowing compound I to undergo a substitution reaction with a dibromospirofluorene conjugated bridge to generate an intermediate II; (b) allowing compound II to undergo a substitution reaction with diethyl phosphite to generate intermediate III; (c) hydrolyzing compound III to generate target product IV, i.e., a self-assembled monolayer material; The reaction equation is shown below Among them, R is a methoxy group or an alkane group, and the conjugated bridge is a spirofluorene-type conjugated bridge.
4. The method for preparing a self-assembled monolayer material with spirofluorene as a conjugated bridge according to claim 3, characterized in that: The specific process of step (a) is as follows: Compound I and the dibrominated conjugated bridge are dissolved in N,N-dimethylacetamide DMAC, and a substitution reaction is carried out under the action of a base and a catalyst to produce an intermediate II; the molar ratio of the compound I to the dibrominated conjugated bridge is 1:1-10.
5. The method for preparing a self-assembled monolayer material with spirofluorene as a conjugated bridge according to claim 3, characterized in that: The specific process of step (b) is: heating compound II and diethyl phosphite to react in a 1,4-dioxane nitrogen atmosphere, and separating and purifying after the reaction to obtain intermediate III; the molar ratio of compound II to diethyl phosphite is 1:1 to 20.
6. The self-assembled monolayer material with spirofluorene as conjugated bridge according to claim 3, characterized in that: In step (c), compound III and bromotrimethylsilane are mixed in dichloromethane, and a hydrolysis reaction is carried out under a nitrogen atmosphere. After the reaction is completed, the target product IV is obtained by slurrying and filtration; the molar ratio of compound III to bromotrimethylsilane is 1:5-15.
7. A method for preparing a self-assembled monolayer material with spirofluorene as a conjugated bridge according to any one of claims 3 to 6, characterized in that: The base used in step (a) is potassium hydroxide or potassium carbonate, the catalyst is cuprous iodide, the reaction temperature is 100-200° C., and the reaction time is 4-12 hours; the reaction temperature in step (b) is 100-110° C., and the reaction time is 4-15 hours; and the reaction temperature in step (c) is 10-100° C., and the reaction time is 4-15 hours.
8. Use of the self-assembled monolayer material with spirofluorene as a conjugated bridge as claimed in claim 1 or 2 in perovskite solar cells.
Citation Information
Patent Citations
Spirofluorene bisbenzoacridine organic semiconductor material, preparation method and use method thereof
CN102229565A
Organic nanomaterial based on spirofluorene-xanthrene mono-substituted carbazole, preparation method and application thereof
CN108610334A
Novel spirofluorene aniline derivative and preparation method thereof
CN109438259A
Aromatic amine derivative, polymer, mixture, composition and organic electronic device
CN109608342A
Self-assembled monomolecular layer hole transport material and preparation method and application thereof
CN118005690A
Cited By
Self-assembled material of carbazole-fluorene derivative and preparation method and application thereof
CN122772017A